Condensed Mode Cooling for Ethylene Polymerization: Part VI. Impact of Induced Condensing Agents on Comonomer Incorporation and Polymer Properties. Issue 6 (30th June 2020) - Ishola, Niyi B.; Andrade, Fabiana N.; Machado, Fabricio; McKenna, Timothy F.L.
Abstract: Gas phase copolymerizations of ethylene and an α‐olefin comonomer are performed using a commercial Ziegler–Natta catalyst in the presence of different induced condensing agents (ICA). The impact of these factors on the yield and final polyethylene properties such as the melt flow index, crystallinity, and incorporation of comonomer is studied. It has been shown that the increase in the rate of polymerization is even more pronounced in the presence of ICA. It also appears that adding ICA to the copolymerizations changes the comonomer incorporation with respect to similar copolymerizations performed without ICA due to competing cosolubility effects. Abstract : Induced condensing agents (ICA) are commonly used to enhance heat removal in gas phase olefin polymerization reactors. ICA can also enhance ethylene solubility in the amorphous phase of polyethylene (PE). It is shown here that different types and quantities of inert ICA can also have a significant impact on the melt flow index and crystallinity of Linear low‐density polyethylene (LLDPE) products